2022
DOI: 10.3389/fpsyg.2022.927458
|View full text |Cite
|
Sign up to set email alerts
|

Proactive Personality and Innovative Work Behavior: Through the Juxtapose of Schumpeter's Theory of Innovation and Broaden-And-Build Theory

Abstract: This study aimed to unfold the implicit interplay of open innovation (OI) and perceived insider status (PIS) between the relationship of proactive personality (PP) and innovative work behavior (IWB). The phenomenon studied the moderated mediation of OI and PIS through the combined optic of the theory of innovation and the broaden-and-build theory. The nature of this study was post-positivist. The two-step approach of structural equation modeling was implemented. First, quantitative data were collected through … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 122 publications
1
6
0
3
Order By: Relevance
“…Furthermore, proactive personalities are change-oriented, which means they prefer to alter the environment around them to better suit their requirements as opposed to merely adjusting to it or adapting it (Li, Gill, Wang, Safdar, & Sheikh, 2022). Such people frequently seek out new, more effective methods of doing things to increase their performance (Li et al, 2022). As a result, the following assertion can be made:…”
Section: Moderating Effect Of Entrepreneurial Educationmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, proactive personalities are change-oriented, which means they prefer to alter the environment around them to better suit their requirements as opposed to merely adjusting to it or adapting it (Li, Gill, Wang, Safdar, & Sheikh, 2022). Such people frequently seek out new, more effective methods of doing things to increase their performance (Li et al, 2022). As a result, the following assertion can be made:…”
Section: Moderating Effect Of Entrepreneurial Educationmentioning
confidence: 99%
“…Greguras and Diefendorff (2010) found that proactive personality and performance have a positive, direct association; as a result, our conceptual model incorporates this direct relationship (see Figure 1). Furthermore, proactive personalities are change-oriented, which means they prefer to alter the environment around them to better suit their requirements as opposed to merely adjusting to it or adapting it (Li, Gill, Wang, Safdar, & Sheikh, 2022). Such people frequently seek out new, more effective methods of doing things to increase their performance (Li et al, 2022).…”
Section: Moderating Effect Of Entrepreneurial Educationmentioning
confidence: 99%
“…This is in line with the statement of (Su & Zhang, 2020) that individuals who exhibit high levels of proactivity are eager to take the lead in proactively seeking valuable information, which in turn promotes the generation of innovative behaviors in a spontaneous manner. Proactive personality is related to individual innovative behavior such as developing new ideas and showing innovations in one field of work (Li et al, 2022). Proactive employees tend to be self-motivated.…”
Section: mentioning
confidence: 99%
“…He created a phrase to describe essence of capitalism in his mind. Therefore, "Creative destruction" has become a most familiar term in economic dictionary [1].…”
Section: New Industriesmentioning
confidence: 99%